Role of Collagen Sheet as a Temporary Cover for Raw Area—An Experimental Study - Dr. R. Krishnan; Dr. T. C. Goel; Dr. S. K. Bhatnagar; Dr. Mahender Kumar (Indian Journal of Plastic Surgery)
1. Collagen sheet is very useful in preventing exogenous infection.